Genetic predisposition to Parkinson's disease:CYP2D6 and HFE in the Faroe Islands - Halling, Jónrit; Petersen, Maria Skaalum; Grandjean, Philippe; Weihe, Pál; Brøsen, Kim (Pharmacogenetics and Genomics, 2008)
OBJECTIVE: To investigate whether the genetic variants of CYP2D6 and HFE are more frequent in Parkinson's disease (PD) patients compared with controls in a population where the prevalence of these variants and PD are increased. METHODS: Blood samples were collected from 79 PD patients and 154 controls in the Faroe Islands. Genotyping for the 'CYP2D6*3, *4, *6 and *9' alleles and for the C282Y and H63D mutations were performed by real-time polymerase chain reaction before Taqman assessment. RESULTS: The frequency of CYP2D6 poor metabolizers among the patients was not higher compared with the frequency found in the control group (χ test, P=0.86). The odds ratio was 0.92 (95% confidence interval: 0.44-1.90). Neither was a difference in HFE genotype or allele frequencies found between the patients and the controls, and the C282Y and H63D mutation carrier frequencies did not reveal any difference (χ test, P=0.50 and 0.60, respectively). CONCLUSION: This study does not support an association between PD and mutations of the CYP2D6 and HFE genes, although a weak association cannot be excluded. The high frequency of PD in the Faroes is most likely the result of interactions between multiple genetic and environmental factors, still to be identified.